Authority and Knowledge in Islamic Intellectual Tradition: A Critical Inquiry into Epistemic Legitimacy in the Age of Information Overload - Syarifudin Syarifudin; Aan Kudrotulloh; Ade Imun Romadan (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2025)
The digital age has brought significant transformations to various sectors, including religious scholarship, where traditional structures of authority are being challenged by the rise of digital media and influencers. This study explores the implications of digital disruption in the Islamic context, focusing on how digital platforms are reshaping authority and epistemic legitimacy. In particular, the emergence of "religious digital creatives" is analyzed, highlighting how these influencers, often with little formal training but significant digital communication skills, have redefined religious authority. This shift away from traditional scholars, such as the ulama, who have been the custodians of religious knowledge, raises concerns about the authenticity and quality of religious teachings disseminated online. The study also examines the role of algorithm driven platforms, like AI-driven tafsir apps, and their impact on Islamic legal derivation and interpretation. While these platforms enhance accessibility, they also present challenges related to standardization and authenticity. By comparing traditional Islamic epistemology, which balances divine revelation, human reason, and scholarly rigor, with the decentralized authority of digital platforms, the study underscores the need for maintaining scholarly integrity and moral responsibility in the digital era. The research also highlights the importance of community trust in traditional scholarship, which is undermined by the lack of accountability in digital content. Ultimately, this study provides a framework for understanding the evolving relationship between Islamic epistemology and digital media, offering recommendations for preserving the core values of traditional scholarship while embracing the opportunities of digital innovation.